Sales management - Simintiras, Antonis C. ([S.l.] : Taylor & Francis, 2007)
Designed to prepare upper-level undergraduate and graduate business students for work in the exciting field of global sales management, this text focuses upon the managerial and cross-cultural aspects necessary for leading the global sales force.
Kindle eBook.